Stress management and psychological resilience of healthcare workers: The role of job satisfaction, job performance, and continuance commitment - Hazal Koray ALAY; Emine OZTURK; Meri TAKSI DEVECIYAN (Journal of Health and Social Sciences)
Introduction: The purpose of this study is to examine the role of job satisfaction, job performance, and continuance commitment in the relationship between psychological resilience and stress management among healthcare workers at İstanbul province public hospitals, in Turkey. Methods: As the data collection and analysis method in this research, a cross-sectional study design was used on a sample of 848 healthcare workers. A simple random sampling method was used to collect data. Data were evaluated using IBM’s statistical program SPSS Statistics 26.0 and Hayes Process Macro statistical program. In the research, data were examined using frequency analysis, explanatory factor analysis, reliability analysis, Pearson correlation analysis, and multiple regression analysis. Result: The research’s findings indicate that stress management, psychological resilience, job satisfaction, and job performance are significantly correlated. There is no statistically significant correlation between continuance commitment and other variables. Discussion: The psychological resilience of health workers is effective on job performance. It is emphasized that the job performance of health workers can help them to have a better level of psychological resilience both personally and professionally. Healthcare workers with high job performance tend to have a more positive relationship with their jobs, which may increase their capacity to cope with stress. Stress management is very important, as healthcare professionals do not accept mistakes and have high risks while providing services. For this reason, stress management practices can be developed to alleviate the difficulties of working conditions in institutions and increase psychological resilience.